Athlete social support, negative social interactions, and psychological health across a competitive sport season - DeFreese, J. D.; Smith, A. L. (Journal of Sport & Exercise Psychology, 2014)
Social support and negative social interactions have implications for athlete psychological health, with potential to influence the links of stress-related experiences with burnout and well-being over time. Using a longitudinal design, perceived social support and negative social interactions were examined as potential moderators of the temporal stress-burnout and burnout-well-being relationships. American collegiate athletes (N = 465) completed reliable and valid online assessments of study variables at four time points during the competitive season. After controlling for dispositional and conceptually important variables, social support and negative social interactions did not moderate the stress-burnout or burnout-well-being relationships, respectively, but did simultaneously contribute to burnout and well-being across the competitive season. The results showcase the importance of sport-related social perceptions to athlete psychological outcomes over time and inform development of socially driven interventions to improve the psychological health of competitive athletes.